Gel Filtration Patterns of Factor VIII Coagulant Antigen and Factor VIII Related Antigen in Normal and von Willebrand’s Disease - Chediak, Juan; Peake, Ian; Bloom, Arthur (Thrombosis and Haemostasis, 1983)
Gel filtration (sepharose 2B CL) patterns of factor VIII coagulant antigen (VIIIC :Ag) and factor VIII related antigen (VIIIR: Ag) were obtained using normal plasma and plasma from patients with von Willebrand’s disease. The latter group consisted of five individuals with normal mobility of factor VIIIR :Ag on cross-immunoelectrophoresis (Type I) and five others with abnormal (increased) mobility (Type II). Results showed that the elution of VIIIC: Ag was delayed in those subjects whose ratio of VIIIR :Ag to VIIIC :Ag was reduced. It has previously been reported that VIIIR :Ag exerts a stabilizing influence on the coagulant activity of factor VIII (VIII: C); our data suggests that when VIIIR :Ag is deficient, abnormal (low molecular weight) forms of VIIIC: Ag circulate.
Keywords: VIII coagulant antigen; von Willebrand’s disease